Penanaman Karakter Peduli Lingkungan Melalui Pengajaran Fikih Ekologi Pada Anak Usia Dini - Fathurahman, M (Institut Agama Islam Negeri Ponorogo, 2021)
This research is a library research, with the title Cultivating Environmentally Concerned Characters through Teaching Ecological Jurisprudence in Early Childhood. This research uses library materials as the main data source, and the main references in this research are ecological and Islamic books, character education and books on early childhood. The purpose of this study is combining two materials at once, namely environmental fiqh material and its role in shaping the character of early childhood. The results showed. First, environmental damage or the current ecological crisis is not actually due to ecological succession factors. However, the damage occurred precisely because of an anthropogenic disaster by human activities. Second, in environmental fiqh it contains material that is very important to study, namely maqoshidu shari'ah, especially hifdzu al-bi'ah. Thirdly, environmental care character is very urgent, especially given to early childhood, and for now studying this section is an obligation.